The effects of ischemia during rest intervals on strength endurance performance - Trybulski, Robert; Bichowska, Marta; Piwowar, Rafal; Pisz, Anna; Krzysztofik, Michal; Filip-Stachnik, Aleksandra; Fostiak, Krzysztof; Makar, Piotr; Wilk, Michal (PloS one, 2023)
BACKGROUND: The study aimed to evaluate the effects of ischemia used during the rest periods between successive sets on maximal number of performed repetitions, time under tension and bar velocity during the bench press exercise. METHODS AND MATERIALS: Thirteen healthy resistance trained men volunteered for the study (age = 28.5 ± 7.1 years; body mass = 87.2 ± 8.6 kg; bench press 1RM = 143.1 ± 20.7 kg; training experience = 11.0 ± 6.9 years). In experimental protocol the subjects performed 5 sets of bench press exercise at 70%1RM with maximal number of repetitions in each and with 5 minutes rest periods between each set. During the ischemia condition occlusion with 80% arterial occlusion pressure (AOP) was applied using a 10 cm wide cuff, before the first set of the bench press exercise and during all rest periods between sets (for 4.5 minute). During the control condition no ischemia was applied. RESULTS: The two-way repeated measures ANOVA showed a statistically significant interaction effect for time under tension (p = 0.022; η2 = 0.20). However, the results did not show a statistically significant interaction effect for peak bar velocity (p = 0.28; η2 = 0.10) mean bar velocity (p = 0.38; η2 = 0.08), and for number of performed repetitions (p = 0.28; η2 = 0.09). The post hoc analysis for interaction showed significantly shorter time under tension for ischemia condition compared to control in set 1 (p < 0.01). The post hoc analysis for main effect of condition revealed that time under tension was significantly shorter for ischemia compared to control condition (p = 0.04). CONCLUSION: The results of this study indicate that ischemia intra-conditioning does not increase strength-endurance performance as well as bar velocity during bench press exercise performed to muscle failure.
Keywords: Male; kosterní svaly; Time Factors; nutriční stav; odpočinek; vzpírání; časové faktory; Humans; mužské pohlaví; Exercise; Rest; Muscle, Skeletal; svalová síla; mladý dospělý; Adult; Young Adult; Resistance Training; odporový trénink; cvičení; Nutritional Status; lidé; dospělí; Muscle Strength; Weight Lifting